HUBUNGAN PELAKSANAAN ROOMING IN PADA IBU NIFAS DENGAN PENINGKATAN FREKUENSI PEMBERIAN ASI DI RSU ROYAL PRIMA MEDAN TAHUN 2022 - Merni Princess Laowo; Tiarnida Nababan; Mitta Diswara; Monarchi R.E.Y. Pardosi; Munira Rusyida; Nidar Hati Laia (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Rooming in is a joint care between a newborn and his mother who is treated in one room in the same room for 24 full hours so that an early infant mother bonding process occurs immediately due to body touch between the baby and mother (Paninsari, 2020). The research method used is cross sectional. The purpose of the study was to determine the relationship between the implementation of rooming in postpartum mothers with the increase in the frequency of breastfeeding at the RSU. Royal Prima Medan. The sample in this study were 30 respondents with purposive sampling technique. Collecting data using observation and questionnaires. The research was conducted from September to October. The results of the study were the majority of respondents aged 31-40 years were 20 people (66.7%), the minority respondents aged 19-30 years were 10 people (33.3%). And the majority of respondents with D3-S1 education are 17 (56.7%) people, while the minority have elementary-high school education as many as 13 (43.3%) respondents. The majority of respondents who gave birth to normal were 25 (83.3%) people, while the minority type of delivery was caesarean section as many as 5 (16.7) respondents. And the majority who did not carry out hospitalization were 16 (53.3%) while the minority who did hospitalization were 14 (46.7%) respondents. The majority of the frequency 8-12 times a day as many as 19 (63.3%) respondents and the minority of the frequency of breastfeeding 2-6 times a day as many as 11 (36.7) respondents. Data analysis using Chi square results obtained by the value of value = 0.000, with a value of value < (0.05). Conclusion There is a significant relationship between rooming in and an increase in the frequency of breastfeeding for postpartum mothers at the Royal Prima Hospital in Medan.